(untitled) (Research, Society and Development, 2021)
This article aims to share the results of an action research of the Educational Robotics and Scratch pilot project for students of Basic Education, in the final years of Elementary School, developed in a state public school in the municipality of Cruz Alta RS, Brazil. The project was designed and organized in the context of the digital culture in which students are inserted, designed in the format of workshops, involving practical activities. The study was based on practical notions of Educational Robotics based on scraps and computational thinking supported by the interactivity tools of the Scratch Software. During the practical workshops, the interest and fluency of the students who participated in the project were observed. The workshops took place on the reverse shift of the students’ regular classes. There were a total of fifteen meetings, over the course of four months. The study was guided by the objective of exploring the knowledge already acquired by students, through their experiences in the face of digital culture and through notions of Educational Robotics and computational thinking, as an incentive to awaken the motivation to new skills such as understanding, thinking, looking for solutions, creativity, judgment, decision making, cooperation and collaboration in group work. The workshops, their objectives and observations are described, in relation to motivation and the acquisition of skills and competences, while the performance of the proposed activities in each one, as well as the perception of students’ prior knowledge in problem solving.